Average acceleration and intensity gradient of primary school children and associations with indicators of health and well-being. Issue 18 (17th September 2019) - Fairclough, Stuart J.; Taylor, Sarah; Rowlands, Alex V.; Boddy, Lynne M.; Noonan, Robert J.
ABSTRACT: Average acceleration (AvAcc) and intensity gradient (IG) have been proposed as standardised metrics describing physical activity (PA) volume and intensity, respectively. We examined hypothesised between-group PA differences in AvAcc and IG, and their associations with health and well-being indicators in children. ActiGraph GT9X wrist accelerometers were worn for 24-h·d −1 over 7days by 145 children aged 9–10. Raw accelerations were averaged per 5-s epoch to represent AvAcc over 24-h. IG represented the relationship between log values for intensity and time. Moderate-to-vigorous PA (MVPA) was estimated using youth cutpoints. BMI z-scores, waist-to-height ratio (WHtR), peak oxygen uptake (VO2 peak), Metabolic Syndrome risk (MetS score), and well-being were assessed cross-sectionally, and 8-weeks later. Hypothesised between-group differences were consistently observed for IG only (p < .001). AvAcc was strongly correlated with MVPA ( r = 0.96), while moderate correlations were observed between IG and MVPA ( r = 0.50) and AvAcc ( r = 0.54). IG was significantly associated with health indicators, independent of AvAcc ( p < .001). AvAcc was associated with well-being, independent of IG ( p < .05). IG was significantly associated with WHtR ( p < .01) and MetS score ( p < .05) at 8-weeks follow-up. IG is sensitive as a gauge of PA intensity that is independent of total PA volume, and which relates to important health indicators in children.